Experience report on the training of Brazilian dental managers using active methodologies. (30th September 2020) - Nacao, M; Machado, V; Ribeiro, S; Barreto, B; Carvalho, M; Witer, A; Fonseca, V
Abstract: This is an account on the training of dental managers in a Social Welfare, not-for-profit, non-governmental institution present in all Brazilian states. Given the continental dimension of Brazil, its regional inequalities and the need for uniformity in the management conduct, as well as in the planning and evaluation of services, it is understood that developing managers' skills and competences is fundamental. Bearing in mind that the model adopted by the company is based on collective health, and its structure is organized in Primary Care, this proposal can be applied by other organizations that offer services of a similar nature. The aim of this study is to describe the training of oral health managers (n = 54) on the themes of sustainability, practices based on evidence/health economics and social determinants - themes that were requested by the managers themselves. Using problem-based learning, active and distance-learning methodologies, three working groups were set up among the managers to go through the contents of the training program, which aimed at training mentors and identifying successful service experiences for sharing. This process peaked at a face-to-face session with all participants where a specialist and their respective mentors presented each topic. The products obtained were: (1) three scientific-economic studies for decision making on the incorporation of hard technologies; (2) a guide to sustainable practices in dentistry and (3) a set of criteria for prioritizing access based on social determinants. In the evaluation of the training, 89% of managers were very satisfied, 8.98% were satisfied and 1.79% were dissatisfied. It is concluded that the methodology used in this process significantly contributed to the development of the company's regional service managers and such improvement stemmed from the empowerment, engagement and alignment of these managers, to which action plans were directed, with measures for monitoring and evaluation. Key messages: Active methodologies in training contributes to the empowerment, engagement and alignment of dental managers before epidemiological, economic and social challenges faced in the management of services. Trainings where the participants are protagonists in all stages of the educational processes, are those that produce the best results and the highest degree of satisfaction among employees.